2016
DOI: 10.1186/s13148-016-0270-x
|View full text |Cite
|
Sign up to set email alerts
|

PITX3 promoter methylation is a prognostic biomarker for biochemical recurrence-free survival in prostate cancer patients after radical prostatectomy

Abstract: BackgroundMolecular biomarkers that might help to distinguish between more aggressive and clinically insignificant prostate cancers (PCa) are still urgently needed. Aberrant DNA methylation as a common molecular alteration in PCa seems to be a promising source for such biomarkers. In this study, PITX3 DNA methylation (mPITX3) and its potential role as a prognostic biomarker were investigated. Furthermore, mPITX3 was analyzed in combination with the established PCa methylation biomarker PITX2 (mPITX2).MethodsmP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…While this model cannot serve as a model for HNSCC tumorigenesis, it is an interesting finding and possibly allows for the implication of PITX3 alteration being an early event in cancer development. This would be in line with the results of Holmes et al, who were able to show that PITX3 methylation is a strong prognostic marker for biochemical recurrence in localized prostate cancer [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…While this model cannot serve as a model for HNSCC tumorigenesis, it is an interesting finding and possibly allows for the implication of PITX3 alteration being an early event in cancer development. This would be in line with the results of Holmes et al, who were able to show that PITX3 methylation is a strong prognostic marker for biochemical recurrence in localized prostate cancer [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…For the training cohort, quantitative PITX3 methylation analysis was performed by means of quantitative real-time PCR (qPCR) with primers and probes as previously described [ 22 ]. The analytical performance of the qPCR assay has been characterized earlier [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…tROC analysis indicated that in patients with PRAD, the AUC of PI-ES was 0.7403 for predicting the cancer status after five years. In addition, the HR of PI-ES for tumor recurrence was 4.097 (95% CI: 2.439-6.881, P=9.77×10 −8 ) according to univariate Cox analysis and 2.599 (95% CI: 1.329-5.084, P=0.005) according to multivariate Cox analysis, which were better than previously reported values focusing on only a single indicator, including programmed death-1 receptor methylation ( 44 ), pituitary homeobox 3 methylation ( 45 ) and cysteine dioxygenase 1 promoter methylation ( 46 ).…”
Section: Discussioncontrasting
confidence: 59%